Perturbations in Lineage Specification of Granulosa and Theca Cells May Alter Corpus Luteum Formation and Function - Abedel-Majed, Mohamed A.; Romereim, Sarah M.; Davis, John S.; Cupp, Andrea S. (Frontiers in Endocrinology, 2019)
Anovulation is a major cause of infertility, and it is the major leading reproductive disorder in mammalian females. Without ovulation, an oocyte is not released from the ovarian follicle to be fertilized and a corpus luteum is not formed. The corpus luteum formed from the luteinized somatic follicular cells following ovulation, vasculature cells, and immune cells is critical for progesterone production and maintenance of pregnancy. Follicular theca cells differentiate into small luteal cells (SLCs) that produce progesterone in response to luteinizing hormone (LH), and granulosa cells luteinize to become large luteal cells (LLCs) that have a high rate of basal production of progesterone. The formation and function of the corpus luteum rely on the appropriate proliferation and differentiation of both granulosa and theca cells. If any aspect of granulosa or theca cell luteinization is perturbed, then the resulting luteal cell populations (SLC, LLC, vascular and immune cells) may be reduced and compromise progesterone production. Thus, many factors that affect the differentiation/lineage of the somatic cells and their gene expression profiles can alter the ability of a corpus luteum to produce the progesterone critical for pregnancy. Our laboratory has identified genes that are enriched in somatic follicular cells and luteal cells through gene expression microarray. This work was the first to compare the gene expression profiles of the four somatic cell types involved in the follicle-to-luteal transition and to support previous immunofluorescence data indicating theca cells differentiate into SLCs while granulosa cells become LLCs. Using these data and incorporating knowledge about the ways in which luteinization can go awry, we can extrapolate the impact that alterations in the theca and granulosa cell gene expression profiles and lineages could have on the formation and function of the corpus luteum. While interactions with other cell types such as vascular and immune cells are critical for appropriate corpus luteum function, we are restricting this review to focus on granulosa, theca, and luteal cells and how perturbations such as androgen excess and inflammation may affect their function and fertility.